1990
DOI: 10.1227/00006123-199001000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Arteriovenous Fistulas Associated with Intraparenchymal Varix in Childhood: Case Reports

Abstract: This report describes three children, each of whom developed an unusual malformation consisting of one or more intracerebral arteriovenous fistulas and a large intraparenchymal venous varix. Their clinical symptoms were similar to those produced by aneurysms of the vein of Galen: increasing head circumference, seizures, hemorrhage, and developmental delay. We treated each child with endovascular embolization and/or surgery and obtained complete closure of all fistulas without mortality. (Neurosurgery 26:122-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Imaging reports and medical records of patients with diagnoses of NGAVF, DAVF, VOGM, and AVM were reviewed. Twenty-eight patients with an NGAVF were identified, including 7 who had been included in other published reports (patients 3,10,11,17,19,20, and 23 of the current series; On-line Table 1). [18][19][20][21] Three patients were excluded due to insufficient clinical and imaging data to confirm the diagnosis of NGAVF.…”
Section: Subjectsmentioning
confidence: 99%
“…Imaging reports and medical records of patients with diagnoses of NGAVF, DAVF, VOGM, and AVM were reviewed. Twenty-eight patients with an NGAVF were identified, including 7 who had been included in other published reports (patients 3,10,11,17,19,20, and 23 of the current series; On-line Table 1). [18][19][20][21] Three patients were excluded due to insufficient clinical and imaging data to confirm the diagnosis of NGAVF.…”
Section: Subjectsmentioning
confidence: 99%
“…The presenting symptoms are documented in the Table. The presentations leading to diagnosis were intracranial hemorrhage, 20 headaches, 21 seizure, 5 and no symptoms (2 patients). The location of the hemorrhage was intracerebral in 1 patient, intracerebellar in 1, and subarachnoid in 2 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The flow and perfusion pressure in pial AVF is high because of the direct arteriovenous shunt, 11) so huge venous varices are not uncommon. 1,3,4,8,20,21) Five of eight patients with conservatively treated pial AVF died. 14) Review of 88 patients with pial AVF found mortality and morbidity rates of 7% and 11%, respectively, following flow disconnection by direct or endovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Second, endovascular treatment risks the migration of embolization material into the draining vein, lung, or elsewhere in the cerebral vasculature. 3,8,12,20) Embolization of a normal vein draining into the venous channel of the pial AVF may result in venous infarction. On the other hand, proximal embolization of the feeder may give rise to new arterial connections and to fistula recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation